EVALUATION OF THE EFFECTS OF CONVENTIONAL RESTRAINT AND ELECTROMAGNETIC IMMOBILIZATION ON STRESS AND WELL-BEING OF CATTLE (International Seven Journal of Multidisciplinary, 2025)
Objective: To evaluate the effects of conventional physical restraint and electromagnetic immobilization on cattle handling, focusing on stress and physiological parameters related to animal welfare. Cattle handling, essential for diagnosis and treatment, can result in considerable stress, manifested by changes in heart rate, cortisol levels, and other biochemical indicators. Conventional restraint techniques, such as the use of ropes and chains, have often been associated with physiological stress reactions, such as increased heart rate and cortisol, which can harm animal welfare and affect productivity. In contrast, electromagnetic immobilization emerges as an alternative, less invasive approach, using electromagnetic waves to keep cattle immobilized more gently. Studies indicate that electromagnetic immobilization can significantly reduce the increase in cortisol levels and decrease adverse reactions to stress, such as increased heart and respiratory rates. In addition, this technique has shown positive results in terms of preserving meat quality and increasing production efficiency, with less metabolic impact. Although electromagnetic immobilization shows promise, the definition of the ideal dose and the proportion of parameters required for its application still require further investigation. The combination of conventional methods with alternative techniques, such as electromagnetic immobilization, may contribute to a more effective approach to cattle management, providing more effective stress control and improved animal welfare.